Persistent organic pollutants in food systems: A comparative study across four contrasting socio-ecosystems: Portugal, Senegal, French Guiana, and Guadeloupe - Nathalie El Deghel; Michael Rapinski; Priscilla Duboz; Richard Raymond; Damien Davy; Nuno Durães; André-Marie Dendievel; Eduardo Ferreira da Silva; Pascal Jean Lopez; Vincent Vaccher; Anaïs Vénisseau; Julie Anne Nazare; et al. (Food Chemistry, 2025)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Temporal pesticide dynamics alter specific eukaryotic taxa in a coastal transition zone - Vincent Hervé; Pierre Sabatier; Josie Lambourdière; Jérôme Poulenard; Pascal Jean Lopez (Science of The Total Environment, 2023)

Global-Scale Environmental Niche and Habitat of Blue Shark (Prionace glauca) by Size and Sex: A Pivotal Step to Improving Stock Management - Jean-Noël Druon; Steven Campana; Frederic Vandeperre; Fábio H. V. Hazin; Heather Bowlby; Rui Coelho; Nuno Queiroz; Fabrizio Serena; Francisco Abascal; Dimitrios Damalas; Michael Musyl; Jon Lopez; et al. (Frontiers in Marine Science, 2022)
Blue shark ( Prionace glauca ) is amongst the most abundant shark species in international trade, however this highly migratory species has little effective management and the need for spatio-temporal strategies increases, possibly involving the most vulnerable stage or sex classes. We combined 265,595 blue shark observations (capture or satellite tag) with environmental data to present the first global-scale analysis of species’ habitat preferences for five size and sex classes (small juveniles, large juvenile males and females, adult males and females). We leveraged the understanding of blue shark biotic environmental associations to develop two indicators of foraging location: productivity fronts in mesotrophic areas and mesopelagic micronekton in oligotrophic environments. Temperature (at surface and mixed layer depth plus 100 m) and sea surface height anomaly were used to exclude unsuitable abiotic environments. To capture the horizontal and vertical extent of thermal habitat for the blue shark, we defined the temperature niche relative to both sea surface temperature ( SST ) and the temperature 100 m below the mixed layer depth ( T mld+100 ). We show that the lifetime foraging niche incorporates highly diverse biotic and abiotic conditions: the blue shark tends to shift from mesotrophic and temperate surface waters during juvenile stages to more oligotrophic and warm surface waters for adults. However, low productivity limits all classes of blue shark habitat in the tropical western North Atlantic, and both low productivity and warm temperatures limit habitat in most of the equatorial Indian Ocean (except for the adult males) and tropical eastern Pacific. Large females tend to have greater habitat overlap with small juveniles than large males, more defined by temperature than productivity preferences. In particular, large juvenile females tend to extend their range into higher latitudes than large males, likely due to greater tolerance to relatively cold waters. Large juvenile and adult females also seem to avoid areas with intermediate SST (~21.7-24.0°C), resulting in separation from large males mostly in the tropical and temperate latitudes in the cold and warm seasons, respectively. The habitat requirements of sensitive size- and sex-specific stages to blue shark population dynamics are essential in management to improve conservation of this near-threatened species.

Arsenic and chlordecone contamination and decontamination toxicokinetics in Sargassum sp. - Damien A. Devault; Félix Massat; Alexandre Baylet; Franck Dolique; Pascal-Jean Lopez (Environmental Science and Pollution Research, 2022)

Sargassum contamination and consequences for downstream uses: a review - Damien A. Devault; Ronan Pierre; Hélène Marfaing; Franck Dolique; Pascal-Jean Lopez (Journal of Applied Phycology, 2021)

Singular physiological behavior of the scleractinian coral Porites astreoides in the dark phase - Pascal Claquin; Malika Rene-Trouillefou; Pascal Jean Lopez; Aurélien Japaud; Yolande Bouchon-Navaro; Sébastien Cordonnier; Claude Bouchon (Coral Reefs, 2021)

Analysis of interdomain taxonomic patterns in urban street mats - Vincent Hervé; Pascal Jean Lopez (Environmental Microbiology, 2020)
Summary Streets are constantly crossed by billions of vehicles and pedestrians. Their gutters, which convey stormwater and contribute to waste management, and are important for human health and well‐being, probably play a number of ecological roles. Street surfaces may also represent an important part of city surface areas. To better characterize the ecology of this yet poorly explored compartment, we used filtration and DNA metabarcoding to address microbial community composition and assembly across the city of Paris, France. Diverse bacterial and eukaryotic taxonomic groups were identified, including members involved in key biogeochemical processes, along with a number of parasites and putative pathogens of human, animals and plants. We showed that the beta diversity patterns between bacterial and eukaryotic communities were correlated, suggesting interdomain associations. Beta diversity analyses revealed the significance of biotic factors (cohesion metrics) in shaping gutter microbial community assembly and, to a lesser extent, the contribution of abiotic factors (pH and conductivity). Co‐occurrences analysis confirmed contrasting non‐random patterns both within and between domains of life, specifically when comparing diatoms and fungi. Our results highlight microbial coexistence patterns in streets and reinforce the need to further explore biodiversity in urban ground transportation infrastructures.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Annual Phytoplankton Primary Production Estimation in a Temperate Estuary by Coupling PAM and Carbon Incorporation Methods - Jérôme Morelle; Mathilde Schapira; Francis Orvain; Philippe Riou; Pascal Jean Lopez; Olivier Pierre-Duplessix; Emilie Rabiller; Frank Maheux; Benjamin Simon; Pascal Claquin (Estuaries and Coasts, 2018)

Physiological adjustments and transcriptome reprogramming are involved in the acclimation to salinity gradients in diatoms - Adrien Bussard; Erwan Corre; Cédric Hubas; Evelyne Duvernois‐Berthet; Gildas Le Corguillé; Laurent Jourdren; Fanny Coulpier; Pascal Claquin; Pascal Jean Lopez (Environmental Microbiology, 2017)
Summary Salinity regimes in estuaries and coastal areas vary with river discharge patterns, seawater evaporation, the morphology of the coastal waterways and the dynamics of marine water mixing. Therefore, microalgae have to respond to salinity variations at time scales ranging from daily to annual cycles. Microalgae may also have to adapt to physical alterations that induce the loss of connectivity between habitats and the enclosure of bodies of water. Here, we integrated physiological assays and measurements of morphological plasticity with a functional genomics approach to examine the regulatory changes that occur during the acclimation to salinity in the estuarine diatom Thalassiosira weissflogii . We found that cells exposed to different salinity regimes for a short or long period presented adjustments in their carbon fractions, silicon pools, pigment concentrations and/or photosynthetic parameters. Salinity‐induced alterations in frustule symmetry were observed only in the long‐term (LT) cultures. Whole transcriptome analyses revealed a down‐regulation of nuclear and plastid encoded genes during the LT response and identified only a few regulated genes that were in common between the ST and LT responses. We propose that in diatoms, one strategy for acclimating to salinity gradients and maintaining optimal cellular fitness could be a reduction in the cost of transcription.